(untitled) (Research, Society and Development, 2022)
Objective: to identify the variables associated with perineal laceration during childbirth care. Method: descriptive-retrospective, documentary, analytical and quantitative study. The sample of 2,217 records of women who underwent eutocic delivery in a public service in the Northeast. Descriptive and inferential analysis of the data and T-student, Chi-square and Phi coefficient tests were carried out. Results: previous cesarean section, use of oxytocin and misoprostol increase the risk of laceration. The T-student test showed that there are differences between the means of the group in which there was laceration regarding the variables “weight of the newborn” and “greater gestational age”, when compared to the group in which there was no laceration. The variables “use of oxytocin” and “vertical position” showed a higher chance of laceration based on the odds ratio measure. Conclusion: Heath professionals who provide assistance to women during pregnancy, delivery and birth must use viable strategies to reduce perineal laceration.